2021
DOI: 10.1111/acel.13499
|View full text |Cite
|
Sign up to set email alerts
|

Changing and stable chromatin accessibility supports transcriptional overhaul during neural stem cell activation and is altered with age

Abstract: Neural stem cells (NSCs) are the source of new neurons, astrocytes, and oligodendrocytes in the adult mammalian brain. Studies in rodents show that adult-born neurons contribute to learning and memory, sensory functions, and mood regulation (Bond et al., 2015).NSCs are located in distinct niches in the subventricular zone (SVZ) of the lateral ventricle and the dentate gyrus of the hippocampus that provide molecular cues for cell proliferation and differentiation. Similar to rodents and non-human primates, NSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 78 publications
2
20
0
Order By: Relevance
“…The chromatin landscape of quiescent NSCs becomes more closed with age whereas that of activated NSCs becomes more open with age. The closing of chromatin regions with age in quiescent NSCs is consistent with observations in cultured NSCs 33 , hair follicle stem cells 83 , and with findings of increased repressive chromatin marks such as H3K27me3 in quiescent stem cells from other niches 84 , including muscle satellite cells 85, 86 and hematopoietic stem cells 87 during aging. In contrast, the chromatin landscape of activated NSCs generally becomes more permissive with age, consistent with the observation that reducing the repressive 5-hydroxymethylcytosine (5hmC) mark in hippocampal NPCs mimics age-dependent defects 28 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The chromatin landscape of quiescent NSCs becomes more closed with age whereas that of activated NSCs becomes more open with age. The closing of chromatin regions with age in quiescent NSCs is consistent with observations in cultured NSCs 33 , hair follicle stem cells 83 , and with findings of increased repressive chromatin marks such as H3K27me3 in quiescent stem cells from other niches 84 , including muscle satellite cells 85, 86 and hematopoietic stem cells 87 during aging. In contrast, the chromatin landscape of activated NSCs generally becomes more permissive with age, consistent with the observation that reducing the repressive 5-hydroxymethylcytosine (5hmC) mark in hippocampal NPCs mimics age-dependent defects 28 .…”
Section: Discussionsupporting
confidence: 87%
“…Epigenomic changes that affect chromatin states play an important role in the regulation of cell fate 26 and aging 27 . So far, however, epigenomic studies of NSCs have been limited to whole tissues in vivo 28, 29 , developmental studies 30 , or culture systems 29, 3133 . Importantly, age- dependent epigenomic changes in different cell types of the neurogenic niche in vivo remain unknown.…”
Section: Main Textmentioning
confidence: 99%
“…For instance, aged NSCs lose chromatin accessibility at regulatory regions of metabolic genes (Maybury-Lewis et al, 2021), suggesting that epigenetic dysregulation during aging could alter NSC metabolic states. Moreover, reduction of lamin B1 protein is widely used as a senescence marker (Fatt et al, 2021;Freund et al, 2012) and could contribute to the observed age-dependent accumulation of hippocampal NSCs with senescence-like characteristics (Fatt et al, 2021).…”
Section: Open Questions and Future Perspectivesmentioning
confidence: 99%
“…CD8+ T cells [9]) and residents somatic stem cells (e.g. neural stem cells [10]). Many other histone modifications and epigenetic mechanisms were linked to aging and longevity [11].…”
Section: Introductionmentioning
confidence: 99%
“…H3K9me3 marks constitutive heterochromatin [17]; H3K27me3, which is associated with promoters of repressed genes [18] and orchestrate development and differentiation [19]; H4K20me3, is associated with repression of transcription when present at promoters [18], is involved in silencing transposons [20], and controls cell senescence and tumors [21]; Deficiency in the H3K4me3 complex results in lifespan extension in worms [22]. The pattern of active enhancers, marked with a combination of H3K27ac & H3K4me1 [23], is also age-dependent [24, 25]. It is likely that information collectively encoded by the above epigenetic marks will be relevant to determine the progress of epigenetic and, perhaps, functional aging.…”
Section: Introductionmentioning
confidence: 99%